Metode Pembelajaran dengan Bermain Peran dalam Pendidikan Triase untuk Mahasiswa Keperawatan - Leli Rezky Dwi Oktavia; Wiwik Kusumawati (Citra Delima : Jurnal Ilmiah STIKES Citra Delima Bangka Belitung, 2019)
The nursing profession requires scientific knowledge, technical abilities and skills. Choosing the right and best teaching method is the most important step in the education process. Role playing is a versatile activity that can facilitate students to learn in real situations. this is a teaching method that has strong and interesting potential to build the skills of nursing students in triage education. Research Objectives: To Provide information about the influence of role-playing method on triage education for nursing students. Method: Sources of research were taken from 3 databases namely PubMed, ProQuest and Ebsco and from Google Scholar using keywords "Role play" or "Role Playing" and "Learning Method" and "Nurse" and "Triage". From the overall results, there are 9 articles that match the inclusion criteria. Results: The 9 articles included in this review. The learning method with role playing influences the nursing students’ communication, cognitive, psychomotor, self reflection, critical thinking and self-efficacy in doing triage process. Conclusion: Role-playing method can facilitate and accommodate increased knowledge and skills. The role-playing method is proven to be able to improve communication, cognitive, psychomotor, self reflection, critical thinking and self-efficacy in nursing triage education. Keywords: Role playing, Learning method, and Triage.